Walāya between Lettrism and Astrology: The Occult Mysticism of Sayyid Ḥaydar Āmulī (d. c. 787/1385) - Mansouri, Mohammad Amin (2020)
Abstract This article examines Sayyid Ḥaydar Āmulī’s occult narratives of sainthood ( al-walāya ) with a focus on his Naṣṣ al-nuṣūṣ fī sharḥ al-fuṣūṣ , a voluminous commentary on Ibn al-ʿArabī’s (d. 638/1240) Fuṣūṣ al-ḥikam . I argue that Āmulī uses lettrism, astrology, and alchemy to construct occult narratives that advocate for the supremacy of sainthood over prophecy ( al-nubuwwa ). I first examine the relation between Āmulī’s lettrism and Shiʿism by concentrating on Shiʿi narratives about the mysterious occult books, Jafr and Jāmiʿa , that are transformed into the macrocosmic and microcosmic books in Āmulī’s work. The focus then shifts to Āmulī’s analysis of the complex relation between alif, bāʾ , and the dot written under bāʾ as the first three components of the basmala formula. As will be seen, Āmulī uses astrology in a similar fashion to illustrate the supremacy of sainthood by associating the heavenly planets with prophecy and the zodiacal signs with sainthood. He also draws on alchemy, or what he identifies as “spiritual alchemy ( al-kīmiyāʾ al-maʿnawī ),” to argue for the supremacy of sainthood.
Keywords: Prophecy; Sainthood; Alchemy; Astrology; Lettrism; Occult sciences